Formation Conditions and Hydrocarbons Generation Potential of Oil Source Rocks of South Tatar Arch and Surrounding Areas - A. S. Khayuzkin; E. V. Morozova; V. P. Morozov; E. A. Korolev; D. M. Favarisova; F. M. Gazeeva; N. A. Nazimov (Georesursy, 2024)
The work studied the lithological and geochemical characteristics of oil and gas source rocks of the central part of the Volga-Ural oil and gas bearing province. The purpose of the work was to reconstruct their formation conditions, study the generation potential and maturity of organic matter, and examine prospects for industrial development. The rocks were studied macroscopically, as well as X-ray analysis, pyrolysis using the Rock-Eval method, SARA analysis, and gas chromatography-mass spectrometry. The formation of the Domanik deposits, Bobrikovsky and Pashiysky horizon mudstones, and Upper Kazan substage clays have all been proven to have occurred in a maritime environment. The content of organic matter in the rocks varies from 0.35 to 11.16%. Minute amounts of organic matter that are difficult to accurately in terms of their geochemical properties can be found in the clayey deposits of the Vereisky and Timan horizons. The Upper Kazan substage clays contain type II/ III kerogen. Mudstones of the Bobrikovsky and Pashiysky horizons, as well as Domanik deposits, contain organic matter represented by type II kerogen. The data obtained may indicate common mechanisms for the accumulation of sapropelic organic matter on the territory of the Volga-Ural basin from Pashian (Frasnian stage) to Bobrikovian (Visean stage) times. It was revealed that the studied deposits are at the stage of catagenesis (PC-MK1). At the same time, Domanik deposits have very good and excellent generation potential, which is characterized by the greatest maturity. Mudstones of the Bobrikovsky horizon have similar generation potential.